Conflict in the Classroom: How Teachers’ Emotional Intelligence Influences Conflict Management - Valente, Sabina; Lourenço, Abílio Afonso (Frontiers in Education, 2020)
Distinct studies showed a positive relationship between emotional intelligence and conflict management. However, there is a lack of research on how teachers’ emotional intelligence influences conflict management in the classroom. Since much more needs to be learned about how teachers' emotional skills related to classroom practice, this research has emerged, and the purpose went to examine how teachers’ emotional intelligence influences classroom conflict management. Moreover, it also was analyzed the relationship between gender, teaching experience and academic training with teachers’ emotional intelligence. The sample comprised of 382 Portuguese teachers. The Emotional Skills and Competence Questionnaire for Teachers, the Rahim Organizational Conflict Inventory II - Portuguese Version in School Context and a personal and professional data inquiry were been used as instruments. Structural equation modeling showed that teachers who tend to have higher levels of emotional intelligence employ more integrating and compromising strategies for conflict management, therefore constructively managing conflict in the classroom. In light of these findings, emotional skills programs should be included in teachers’ academic training to promote their emotional intelligence and give them tools to constructively manage classroom conflict.